Factors Associated with the Delay in Seeing a Doctor: Evidence of Chinese Middle-Aged and Older Adults - Qin S; Ni X; Ding Y (Journal of Multidisciplinary Healthcare, 2023)
Shangren Qin,1 Xiaoyan Ni,2 Ye Ding3 1School of Public Health, Hangzhou Normal University, Hangzhou, Zhejiang, People’s Republic of China; 2Cangqian Street Community Health Service Center, Hangzhou, Zhejiang, People’s Republic of China; 3School of Public Health, Hangzhou Medical College, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Ye Ding, School of Public Health, Hangzhou Medical College, 8 Yikang Street, Hangzhou, 311399, People’s Republic of China, Tel +86-571-87692813, Email dingye729@126.comconvenienBackground: There have been few studies concerning delayed medical attention among middle-aged and older adults, and in-depth analyses of delay duration and symptoms have been lacking.Methods: In this cross-sectional study exploiting a face-to-face questionnaire survey, we investigated delays in seeing a doctor among ≥ 45-year-old people in Zhejiang, China over the past year, and analyzed relevant influencing factors through logistics regression.Results: A total of 1034 people aged ≥ 45 years were enrolled, whose overall occurrence of delay in seeing a doctor was 28.24% (23.00% for older adults aged ≥ 60 years). Factors like the presence of 2 chronic diseases, intense social loneliness, and more health care needs contributed to the occurrence of delay in seeing a doctor (OR (95% CI) = 2.102 (1.252– 3.529); OR (95% CI) = 1.030 (1.002– 1.059); OR (95% CI) = 1.049 (1.002– 1.099). Contrastively, factors like convenient access to medical care and good self-reported health status inhibited such occurrence OR (95% CI) = 0.321 (0.199– 0.519); OR (95% CI) = 0.369 (0.183– 0.745). The foremost reason was wanting to wait and see if the problem would get better on its own (117, 40.07%). Respiratory system disease (14.90%), dental problems (13.82%), and cardiac disease (13.61%) constituted the top 3 types of diseases whose treatments were delayed. Additionally, for the majority of older adults, the delay duration was 1– 2 weeks (99, 33.90%), and the economic burden was the cause of the longest delay in seeing a doctor among middle-aged and older adults.Conclusion: To alleviate the problem of delay in seeing a doctor among middle-aged and older adults, their families and society should enhance care for them and reduce their sense of social loneliness. Emphasis should be placed by the government on helping middle-aged and older adults with financial difficulties so that their medical convenience can be improved.Keywords: middle-aged, older adults, delaying doctor visits, China, cross-sectional study